A micrometeorology study of stock watering ponds, rangelands, and woodlands in the Flint Hills of Kansas - Duesterhaus, Jamey L. (Kansas State University, 2008)
Land management practices such as burning and grazing may affect evapotranspiration (ET) and water balance of the tall grass prairie in the Flint Hills of eastern Kansas. Experiments were designed to estimate or measure the water balance of a stock-watering pond, and compare energy balance parameters and ET between grazed and ungrazed prairies. The hydrology of the native tallgrass prairie also was compared with mature stand of eastern red cedar (Juniperus virginiana), a site that was formerly prairie but converted to woodland when prescribed burning was discontinued. Data were collected to encompass the seasonal and yearly changes in weather variability. A host of micrometeorological sensors were used to measure surface atmosphere exchange and water losses, including: eddy covariance towers on prairie and woodland sites, specialized through fall and stem flow equipment at the woodland site, and an instrumentation raft at the stock watering pond. Results of the stock pond study showed that, on average, evaporation accounted for 64% of the water loss, followed by seepage at 31%, cattle use at 3% and transpiration at 2%. Comparisons of grazed and ungrazed areas showed that grazing caused only small, 3 to 6 %, reductions in seasonal ET compared with ungrazed pastures despite large differences in vegetative cover. In the woodland study, the 50-yr-old cedar canopy intercepted 54% of the precipitation received, thus decreasing the amount of precipitation reaching the soil. Evapotranspiration from woodland and prairie sites were similar, but net carbon exchange was greater on the prairie. Thus, the apparent water use efficiency during he summer months was 3 times greater on the prairie. Net radiation at the woodland site was 100 W m-2 higher compared with the prairie. This caused an increase in the woodland sensible heat flux and midday Bowen ratios, yet woodland latent heat flux and ET was similar to the prairie during the study, factors that could affect regional climate. Land management decisions regarding grazing, prescribed burning, and stock pond design will impact the watershed hydrology and productivity of the tallgrass prairie.
Keywords: evaporation; stockpond; evapotranspiration; Agriculture, Agronomy (0285); Agriculture, Range Management (0777); Engineering, Agricultural (0539)